«An I that is really a We». Around the idea of a third Spain in Miguel de Unamuno’s thought - Erquiaga Martínez, Cristina (Historia y Política, 2025)
The idea of the existence of two Spains appears frequently in Miguel de Unamuno’s work. It directly derives from the dualist perspective with which he often viewed existence and according to which he considered that the key to life lies in the confrontation between two realities. Thus, for the Basque intellectual, national life necessarily results from the conflict between two Spains, which acquire different characterisations depending on the issue in dispute or the period under analysis. From this approach, this paper aims to explore how the idea of a third Spain might fit into Unamuno‘s thought as a whole. Through an overview of the development of his interpretation of the confrontation between the two Spains, and an analysis of notions closely linked to it such as civil war, uncivil war, anti-Spain, alterutralidad, and hunos y hotros, this work offers a reflection on whether or not this central concept of Spanish recent history can be found in Unamuno.